The Effect of Radiation Therapy Complexity Planning on Survival of Elderly Patients with Unresected Localized Lung Cancer - Park, Chang H. (2010)
PURPOSE: Radiation therapy (RT) is the standard treatment for patients with unresected stage I–II non-small cell lung cancer (NSCLC). Complex radiation simulation and planning is frequently used to achieve higher RT doses while reducing toxicity, but its impact on survival remains unclear. The objective of this study was to evaluate if complex RT planning was associated with improved outcomes in a cohort of elderly patients with unresected stage I–II NSCLC. METHODS & MATERIALS: Using the Surveillance, Epidemiology, and End Results registry linked to Medicare claims, we identified 1,998 patients aged >65 years with histologically confirmed, unresected stage I–II NSCLC. Patients were classified into an intermediate or complex RT planning group using Medicare physician codes. To address potential selection bias, we used propensity score modeling. Survival of patients who received intermediate and complex simulation was compared using Cox regression models adjusting for propensity scores and in a stratified and matched analysis according to propensity scores. RESULTS: Overall, 25% of patients received complex RT planning. Complex RT planning was associated with better overall (hazards ratio [HR]: 0.84; 95% confidence interval [CI], 0.75–0.95) and lung cancer specific (HR: 0.81; 95% CI, 0.71–0.93) survival after controlling for propensity scores. Similarly, stratified and matched analyses showed better overall and lung cancer-specific survival of patients treated with complex RT planning. CONCLUSIONS: The use of complex RT planning is associated with improved survival among elderly patients with unresected stage I–II NSCLC. These findings should be validated in prospective randomized controlled trials.